Relationship Between Growth Mindset and English Language Performance Among Chinese EFL University Students: The Mediating Roles of Grit and Foreign Language Enjoyment - Hu, Xiaoyu; Sidhu, Gurnam Kaur; Lu, Xin (Frontiers in Psychology, 2022)
There is no denying that there is ample evidence of numerous factors that influence language learners’ success. Recently, there is a critical call to embrace positive psychology that is more open and appreciative of the positive influences in learning English as a foreign language (EFL). Therefore, this paper puts forward the findings of a study that aimed to examine the mediating roles of grit and foreign language enjoyment in the relationship between growth mindset and English language performance. The study employed a correlational research design involving 388 EFL students from one university in China. The data were collected through a questionnaire and an English language performance test. Using the structural equation modeling, this study found that the association between growth mindset and English language performance was partially mediated by grit and foreign language enjoyment. This indicates that students with a growth mindset tend to possess a higher level of grit as well as experience more enjoyment in learning English, which consequently can lead to students becoming more successful language learners. These findings provide significant implications for language teachers, educational material developers, and school administrators in China to embrace the affective domain postulated by positive psychology.